Post-traumatic neuropathic pain: a descriptive review - Ana Cristina Pinho Lopes da Mota (2018)
Introduction and objectives: Trauma related neuropathic pain (TrNP), is a very debilitating condition, which can be caused by a variety of situations. TrNP is considered a social and economic problem and it´s usually refractory to a variety of therapeutic modalities. Little is known about TrNP pathophysiology and best treatment. The aim of this article is to summarize the current knowledge developed in recent years about TrNP. Methods: A query in Pubmed database was performed for the following terms "Neuropathic pain" and "Trauma" and research papers from the last decade with an available English abstract were included. Other articles considered to be relevant to this issue but published out of the referred time span were also included. Results: In our search we´ve encountered few studies addressing this issue the majority of them focusing on TrNP after spinal cord injury. TrNP can be caused by central, peripheral and mixed mechanisms and it´s usually subdivided according to the type of injury or it can result in syndromes like complex regional pain syndrome. TrNP clinical presentation is similar to other neuropathic pain entities. TrNP has no specific treatment however new TrNP therapeutic targets that can act in a more specific way are being developed. Conclusion: TrNP is a condition poorly characterized in terms of classification, epidemiology and pathophysiology and in literature there are few studies addressing this issue. More research of TrNP specific pathophysiology and treatment targets is needed in order to find a better management of this limiting condition.